Clinical Characteristics and Immune Responses of 137 Deceased Patients With COVID-19: A Retrospective Study - Cui, Ning; Yan, Rongdi; Qin, Chunyuan; Zhao, Jingming (Frontiers in Cellular and Infection Microbiology, 2020)
Objective: To evaluate the factors associated with death in patients with COVID-19 by clarifying the clinical characteristics and immune responses. Methods: Clinical characteristics and laboratory findings, including cytokines and lymphocyte subsets, were obtained from electronic medical records of patients at a Wuhan hospital. Results: The study included 836 patients with confirmed COVID-19. A total of 699 enrolled patients (83.6%) were cured and discharged, and 137 patients (16.4%) died. Our analysis revealed that age ≥ 65 years, male sex, malignancy, chronic obstructive pulmonary disease, dyspnoea, dizziness, respiratory rate > 20 bpm, heart rate > 100 bpm, systolic blood pressure < 90 mmHg, neutrophils > 6.3×109/L, lymphopenia, thrombocytopenia, D-dimer ≥ 0.5 mg/L, lactate dehydrogenase > 250 U/L, aspartate aminotransferase > 40 U/L, total bilirubin > 26 μmol/L, albumin < 35 g/L, blood urea nitrogen > 9.5 mmol/L, estimated glomerular filtration rate < 90 ml/min/1.73, elevated cardiac troponin I, N-terminal pro-brain natriuretic peptide ≥ 900 pg/mL, C-reactive protein ≥ 25 mg/L, procalcitonin ≥ 0.05 ng/mL and ferritin > 400 μg/L were associated with the death of patients with COVID-19. Multivariate logistic regression analysis revealed that estimated glomerular filtration rate < 90 ml/min/1.73, elevated cardiac troponin I, C-reactive protein ≥ 25 mg/L and procalcitonin ≥ 0.05 ng/mL were predictive of mortality. Regarding immune responses, IL-2R, IL-6, IL-8, IL-10 and TNFα on admission were remarkably higher in the deceased group, and the levels of IL-2R, IL-6, IL-8, IL-10 and TNFα in the deceased group showed a rapid increase; the dynamics of these cytokines were highly consistent with disease deterioration. Analysis of lymphocyte subsets revealed that deceased patients showed significant decreases in lymphocyte counts, especially helper T cells, suppressor T cells and NK cells. Conclusions: This study identified that estimated glomerular filtration rate < 90 ml/min/1.73, elevated cardiac troponin I, C-reactive protein ≥ 25 mg/L and procalcitonin ≥ 0.05 ng/mL were predictors for mortality in COVID-19 patients. Elevated cytokine levels and the trend of continued increase, such as IL-2R, IL-6, IL-8, IL-10 and TNFα, and decreased lymphocyte subsets, especially helper T cells, suppressor T cells and NK cells, were associated with poor prognosis of COVID-19.